2020
DOI: 10.1108/jfra-03-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of AAOIFI governance disclosure in Islamic banks

Abstract: Purpose The purpose of this study is to investigate the influence of corporate governance mechanisms on Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) governance disclosure in Islamic Banks. Design/methodology/approach To test the research hypotheses, the authors created a comprehensive AAOIFI governance disclosure index and used regression analysis for a sample of Islamic banks for the financial years within the period 2013-2015. Findings The authors found that audit commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 62 publications
9
52
2
1
Order By: Relevance
“…It is proven by the regression results of the sig value 0.0002 <0.05 and a positive coefficient of 0.424. This result is in line with previous research conducted by Glaum et al (2013), Samaha et al (2012), Sellami &Tahari (2017), andElgattani (2020). The results of this study provide empirical evidence that the existence of an audit committee is an important variable affecting the level of sharia compliance in Sharia banks.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is proven by the regression results of the sig value 0.0002 <0.05 and a positive coefficient of 0.424. This result is in line with previous research conducted by Glaum et al (2013), Samaha et al (2012), Sellami &Tahari (2017), andElgattani (2020). The results of this study provide empirical evidence that the existence of an audit committee is an important variable affecting the level of sharia compliance in Sharia banks.…”
Section: Resultssupporting
confidence: 92%
“…The results of this study are inconsistent with agency theory. These results support previous research conducted by Elgattani (2020) that liquidity does not positively affect the disclosure of AAOIFI Governance in Sharia banking. In this study, it can be concluded that the first hypothesis, which states that liquidity has a positive effect on the level of sharia compliance of Sharia banks, is not supported.…”
Section: Resultssupporting
confidence: 92%
“…These findings confirm that the corporate disclosure degree has no effect on the performance of the UAE Islamic banks. However, Elgattani and Hussainey (2020) showed an insignificant impact between AAOIFI and the financial performance. These authors studied the influence of the AAOIFI disclosure on the IBs performance in eight countries that adopted mandatory AAOIFI standards for the years 2013-2015 through using the OLS regression analysis.…”
Section: The Impact Of Disclosure On Financial Performancementioning
confidence: 86%
“…Finally, some studies propose that older banks were more efficient than younger ones because their members are more experienced and more qualified. In accordance with some earlier works, we calculate the bank size (SIZE) as the natural logarithm of the total assets (Ajili and Bouri, 2018;Elgattani and Hussainey, 2020). The bank leverage (LEV) is measured by the total debt ratio to total assets (Abdul Rahman and Bukhair, 2015).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation